Horizontal Diversification with Cayenne Pepper and Tomato and Its Farm Income Implications in Minahasa Regency. - Rori, Yolanda P. I.; Lumingkewas, Jelly R. D.; Sondakh, Mex Frans L.; Benu, Noortje Marsellanie (Jurnal Agroekoteknologi Terapan (JAT), 2025)
Cayenne pepper and tomato are important horticultural crops for smallholder farmers in North Sulawesi, Indonesia, yet their role within horizontally diversified farming systems is not well documented. This study analyses horizontal crop diversification as a strategy for strengthening household economies in Taraitak Satu Village, North Langowan District, Minahasa Regency. An exploratory case-study design was used, combining descriptive quantitative and qualitative approaches. Primary data were collected through structured interviews with ten purposively selected farmers who simultaneously cultivated cayenne pepper (Capsicum frutescens L.) and tomato (Solanum lycopersicum L.) on the same land during one production season. Information on land area, input use, production costs, yields, prices, revenues and capital sources was used to construct farm budgets for the diversified system. The results show that most farmers operate on less than 0.5 ha, yet the combined cayenne–tomato system generates relatively high net farm income. Total production cost for the ten farmers amounted to IDR 120,428,163, while total revenue reached IDR 905,842,000, resulting in a total net income of IDR 785,413,837. Individual net incomes ranged from IDR 21,965,000 to IDR 195,007,000 per season, with an average of about IDR 78.5 million per farmer. Some farmers relied on formal bank credit to finance input purchases and labour, reflecting the link between diversification and access to capital. The findings suggest that horizontal diversification with cayenne pepper and tomato can provide substantial income under favourable conditions, although the small sample size and single-season data mean that results should be interpreted as indicative rather than generalisable. Keywords: horizontal diversification; cayenne pepper; tomato; farm income; smallholder farmers.